2018
DOI: 10.1038/nrrheum.2018.33
|View full text |Cite
|
Sign up to set email alerts
|

Update on outcome assessment in myositis

Abstract: The adult and juvenile myositis syndromes, commonly referred to collectively as idiopathic inflammatory myopathies (IIMs), are systemic autoimmune diseases with the hallmarks of muscle weakness and inflammation. Validated, well-standardized measures to assess disease activity, known as core set measures, were developed by international networks of myositis researchers for use in clinical trials. Composite response criteria using weighted changes in the core set measures of disease activity were developed and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 139 publications
(188 reference statements)
2
82
0
1
Order By: Relevance
“…The predictive role of MYOACT score in this study might lie in the partially overlapped pathological mechanism between AE-ILD and IIM. Elevated levels of several cytokines and chemokines, namely IL-6, IL-8, IL-17, IL-23, etc., were seen in peripheral blood, muscle or skin of IIM patients, and were consistent with disease activity (37). Meanwhile several studies also observed significant elevation of cytokines and chemokines including IL-6, IL-8 in patients with ILD exacerbation, and the elevation was found to be related to worse outcome (38,39).…”
Section: Discussionsupporting
confidence: 58%
“…The predictive role of MYOACT score in this study might lie in the partially overlapped pathological mechanism between AE-ILD and IIM. Elevated levels of several cytokines and chemokines, namely IL-6, IL-8, IL-17, IL-23, etc., were seen in peripheral blood, muscle or skin of IIM patients, and were consistent with disease activity (37). Meanwhile several studies also observed significant elevation of cytokines and chemokines including IL-6, IL-8 in patients with ILD exacerbation, and the elevation was found to be related to worse outcome (38,39).…”
Section: Discussionsupporting
confidence: 58%
“…MSAs were detected by standardized immunoprecipitation and immunoprecipitation-immunoblot methods (34) at the NIH Clinical Center Central Laboratory. Clinical characterization and measurements of IIM disease activity and damage were obtained as previously described (35,36). Videocapillaroscopy was quantified as described previously (37).…”
Section: Methodsmentioning
confidence: 99%
“…As a core set measure for IIM patients, MYOACT score work as an overall assessment of IIM disease activity by taking muscular and various extra-muscular manifestations into consideration. It has been demonstrated to predict outcome of IIM patients and re ect in ammatory level [47,48]. Meanwhile RP-ILD was also found to be associated with cytokines like tumor necrosis factor, etc [49].…”
Section: Discussionmentioning
confidence: 97%